2018
DOI: 10.1007/s00441-018-2968-x
|View full text |Cite
|
Sign up to set email alerts
|

The cell–cell junctions of mammalian testes: II. The lamellar smooth muscle monolayer cells of the peritubular wall are laterally connected by vertical adherens junctions—a novel architectonic cell–cell junction system

Abstract: The testes of sexually mature males of six mammalian species (men, bulls, boars, rats, mice, guinea pigs) have been studied using biochemical as well as light and electron microscopical techniques, in particular immunolocalizations. In these tissues, the peritubular walls represent lamellar encasement structures wrapped around the seminiferous tubules as a bandage system of extracellular matrix layers, alternating with monolayers of very flat polyhedral Blamellar smooth muscle cells^(LSMCs), the number of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 143 publications
(171 reference statements)
1
5
0
Order By: Relevance
“…Striatin is expressed in diverse cellular and subcellular compartments such as the medium spiny neurons in the striatum (Benoist et al, 2006) and membrane-bound signaling complexes (Lu et al, 2004). Other studies, as well as ours, have shown that striatin is also expressed in junctions between epithelia cells (Breitman et al, 2008;Domke et al, 2014;Franke et al, 2015;Domke and Franke, 2019;Lahav-Ariel et al, 2019). Interestingly, striatin has been shown to be expressed in different types of cell junctions.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Striatin is expressed in diverse cellular and subcellular compartments such as the medium spiny neurons in the striatum (Benoist et al, 2006) and membrane-bound signaling complexes (Lu et al, 2004). Other studies, as well as ours, have shown that striatin is also expressed in junctions between epithelia cells (Breitman et al, 2008;Domke et al, 2014;Franke et al, 2015;Domke and Franke, 2019;Lahav-Ariel et al, 2019). Interestingly, striatin has been shown to be expressed in different types of cell junctions.…”
Section: Introductionsupporting
confidence: 63%
“…In addition, striatin has been shown to colocalize with β-catenin, a junctional protein, in different tissues (Domke et al, 2014;Franke et al, 2015;Domke and Franke, 2019). However, as our previous studies indicate that in the mammalian cells tested striatin did not bind or colocalize with β-catenin (Breitman et al, 2008) and that in the inner ear β-catenin is barely seen in hair cells (Liu et al, 2016), the possibility that striatin and β-catenin interact was not examined in the current study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In situ, these cells and extracellular matrix form the peritubular compartment of the seminiferous tubules. The cells express smooth muscle actin (ACTA2), calponin (CNN1), and other typical cytoskeletal markers, as well as a number of genes for specific extracellular matrix proteins [10]. Accordingly, for example, the extracellular matrix of the peritubular cell wall contains, among others, collagens and elastin (ELN; see images in the Human Protein Atlas; [11]).…”
Section: Introductionmentioning
confidence: 99%
“…PM cells together with the basement membrane (BM) constitute a physical barrier that provides structural support of the STs [4]. One of the main components of this physical barrier is vimentin [5].…”
Section: Introductionmentioning
confidence: 99%